2014
DOI: 10.1177/1474515113519930
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported health status in coronary heart disease patients: A comparison with the general population

Abstract: CHD has a negative influence on patient's self-reported health status, both the EQ-VAS as well as the EQ-5D dimensions (with the exception of self-care in both genders and pain/discomfort in males) were impaired. The relative impairment was the greatest in female patients and the differences in the proportion of reported problems diminished with increasing age. The EQ-5D instrument is appropriate in capturing problems related to anxiety/depression, pain/discomfort, mobility and usual activities. Within clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
20
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 44 publications
3
20
0
1
Order By: Relevance
“…In fact, family health depends on woman’s health. Previous studies reported that in comparison to the general population, patients with CAD had lower QOLs (19, 20). Our finding was supported by Durmaz et al study; they reported that the average level of overall QOL score measured by QLI in patients with CAD was 16.0 ± 0.94 (16).…”
Section: Discussionmentioning
confidence: 89%
“…In fact, family health depends on woman’s health. Previous studies reported that in comparison to the general population, patients with CAD had lower QOLs (19, 20). Our finding was supported by Durmaz et al study; they reported that the average level of overall QOL score measured by QLI in patients with CAD was 16.0 ± 0.94 (16).…”
Section: Discussionmentioning
confidence: 89%
“…6,7,23,30,36,45 Generic instruments enable comparison with nondermatological diseases. The impairment for several skin conditions is similar to the reduced HRQoL caused by diabetes mellitus, 20 cardiovascular disease, 16,17 COPD, 19 arthritis pain, 15 anxiety, 21 some cancers, 16,18 renal and liver diseases, 16 visual impairment, 16 and cytostatic, other or no treatment of CLL. [15][16][17][18][19][20][21][22] See Appendix S4 (online Supporting Information) for a detailed description of these studies.…”
Section: Discussionmentioning
confidence: 89%
“…13,14 Leg ulcers, HS, blistering diseases and prurigo had the lowest means (< 60) similar to rheumatoid arthritis pain (56Á4), 15 cardiovascular disease (37- 89), 16,17 cancer (48Á0-84Á0), 16,18 liver disease (57-70) 16 and chronic obstructive pulmonary disease (COPD; 54Á7-58Á8). 19 The impairment in mean self-reported health for other chronic skin diseases (psoriasis, atopic eczema, pruritus, hand eczema, connective tissue disease and genital conditions) showed mean values < 70, similar to diabetes mellitus (68Á8), 20 cardiovascular disease (37-89), 16,17 anxiety (63Á8), 21 cancers (48Á0-84Á0), 16,18 liver disease (57-70), 16 chronic lymphocytic leukaemia (CLL; 70Á3-77Á6) 22 and visual impairment (64Á0-82Á0). 16 As comorbidity was adjusted for, the data indicate how skin disease alone impairs self-reported health.…”
Section: Discussionmentioning
confidence: 98%
“…In patients with coronary artery disease, an impaired HRQoL has been reported with problems on several dimensions of the EQ-5D except for self-care. 31 This discrepancy regarding self-care may be due to a difference in time after the event. Because our patients were in the acute phase after their event (G6 months), problems regarding self-care were more likely than at a later stage as in the previous study.…”
Section: Discussionmentioning
confidence: 98%
“…Because our patients were in the acute phase after their event (G6 months), problems regarding self-care were more likely than at a later stage as in the previous study. 31 Perhaps more important than self-care were the reported problems on anxiety and depression. Strikingly, only the severe problems did have an impact on dropout.…”
Section: Discussionmentioning
confidence: 99%